The Effect of the Extinction Procedure in Function-Based Intervention. (April 2013) - Janney, Donna M.; Umbreit, John; Ferro, Jolenea B.; Liaupsin, Carl J.; Lane, Kathleen L.
In this study, we examined the contribution of the extinction procedure in function-based interventions implemented in the general education classrooms of three at-risk elementary-aged students. Function-based interventions included antecedent adjustments, reinforcement procedures, and function-matched extinction procedures. Using a combined ABC and reversal phase design (A-B-A-B-C-B), a functional relation between the full intervention and dramatically improved levels of on-task behavior were clearly established. On removal of the extinction procedure, on-task behavior rapidly dropped to lower levels. Reinstatement of the full intervention occurred following the partial intervention condition. In every case, on-task levels rapidly improved. Using the Intervention Rating Profile–15 and Children's Intervention Rating Profile, acceptability ratings were highest for full intervention. Limitations and implications for further research are presented.